Out of school children and child protection: Understanding and improving the quality of data on out of school children - William C. Smith (Child Protection and Practice)
This practice perspective article focuses on an at-risk group often in need of further support and protection, out of school children. To evaluate whether child protection services are meeting the needs of our out of school children, reliable, accurate data is needed. However, measures of the out of school population are either missing or inconsistent. In this discussion I review some of the reasons why estimates may differ - comparing two of the most common sources of measurement, administrative data and household survey data. Sampling frames, definitional challenges, and data processing procedures are considered. I end this brief article with recommendations to improve the monitoring of out of school children through improved data collection, data alignment, and data reporting.